INVESTIGATING EFL PRE-SERVICE TEACHERS’ PERCEPTIONS OF TPACK (TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE) FOR THEIR TEACHING - Nur Alifatun Nisa (Journal of English Education Program (JEEP), 2022)
This study focused on EFL pre-service teachers’ perceptions of TPACK (Technological Pedagogical Content Knowledge) for their teaching English education students at a private college in Ciamis, Indonesia. A survey study was used as a research design. The writer purposively selected 35 pre-service teachers (11 male and 24 female students) as the participants. The questionnaires were used as the research instrument in this study. This study used exploratory data analysis to analyze the data. The conclusions revealed that TK, TPK, and TPC were informed the highest percentages followed by Pedagogical Knowledge (PK), Content Knowledge (CK), Pedagogical Content Knowledge (PCK), and Technological Content Knowledge (TCK). It also revealed that they implemented their TPACK which mostly focuses on technological knowledge rather than pedagogical knowledge.